Social Adjustment In School In Adolescents Who Have School Bulying - Alifia Ridha Pratiwi (Institute of Computer Science (IOCS), 2020)
The experience of school bullying or bullying at school is one of the factors that can affect social adjustment, especially social adjustment at school. Adolescents who are victims of bullying will experience psychological distress (psychological distress) which directly becomes an obstacle in making social adjustments. This study aims to see the description of social adjustment at school in adolescents who experience school bullying. This study was conducted on three teenagers who experienced bullying at school using a qualitative approach. The theory used in this study is the theory of social adjustment in schools by Schneiders (1964). Social adjustment is considered as important for adolescents to be able to fulfill their developmental tasks. The results showed that the three research subjects had poor social adjustment in school. Subject F has poor social adjustment in school in terms of completing school assignments, following lessons in class, and interacting with friends in class. Subject T has a poor social adjustment in school in terms of interacting with his friends in class. Meanwhile, subject M has poor social adjustment in school in terms of following lessons in class, completing school assignments, interacting with friends, and attending school. School environment factors and parenting patterns are considered very influential on the good or bad social adjustment in school in the three subjects. Subject F has poor social adjustment in school in terms of completing school assignments, following lessons in class, and interacting with friends in class. Subject T has a poor social adjustment in school in terms of interacting with his friends in class. Meanwhile, subject M has poor social adjustment in school in terms of following lessons in class, completing school assignments, interacting with friends, and attending school. School environment factors and parenting patterns are considered very influential on the good or bad social adjustment in school in the three subjects. Subject F has poor social adjustment in school in terms of completing school assignments, following lessons in class, and interacting with friends in class. Subject T has a poor social adjustment in school in terms of interacting with his friends in class. Meanwhile, subject M has poor social adjustment in school in terms of following lessons in class, completing school assignments, interacting with friends, and attending school. School environment factors and parenting patterns are considered very influential on the good or bad social adjustment in school in the three subjects. Subject T has a poor social adjustment in school in terms of interacting with his friends in class. Meanwhile, subject M has poor social adjustment in school in terms of following lessons in class, completing school assignments, interacting with friends, and attending school. School environment factors and parenting patterns are considered very influential on the good or bad social adjustment in school in the three subjects. Subject T has a poor social adjustment in school in terms of interacting with his friends in class. Meanwhile, subject M has poor social adjustment in school in terms of following lessons in class, completing school assignments, This is an open interacting with friends, and attending school. School environment factors and parenting patterns are considered very influential on the good or bad social adjustment in school in the three subjects.